KOKEMAN Game Model Effectiveness in Enhancing Elementary Students' Learning Interest - Bintang Aura Dewi; Indra Safari; Dewi Susilawati (Universitas Negeri Semarang, 2026)
Low participation in physical activity is a global issue that is often rooted in the failure of conventional Physical Education (PJOK) in building students' interest in learning from an early age. This study aims to analyze the influence of the physical fitness collaboration game model (KOKEMAN) on PJOK learning interest in elementary school students. The research method used was a quasi-experiment with a non-equivalent control group design involving 20 grade V students at SDN Rancakalong. Interventions were carried out in 14 meetings with tested protocols. Data was collected through a validated interest questionnaire with an expert judgment score of 94% and a reliability of 0.801. The results of the Paired Samples T-Test showed a very significant increase in the experimental group with a significance value (p=0.000). Furthermore, analysis of the N-Gain score showed that the experimental group achieved an increase of 48% in the medium category, far exceeding the control group which only reached 10% in the low category. In conclusion, Kokeman's game model has proven to be effective in significantly increasing students' interest in learning through the creation of a joyful learning environment. These findings confirm that the integration of structured play elements from an early age is a crucial preventive step to prevent understanding gaps and low interest in movement that can persist into adulthood.